Estudio hidrológico y socioeconómico Valle de Jalapa - Gutiérrez, M.; Aguilar Velásquez, A.; Sotelo, H.; Rodríguez Martínez, P.; Acevedo Martínez, Y.; Valle, J. (Estelí (Nicaragua), 2000)
Sumario (Es)
Ilus.
Keywords: HIDROLOGIA; RIEGO; ASPECTOS FISIOGRAFICOS; ENTORNO SOCIOECONOMICO; GEOLOGIA; CLIMATOLOGIA; NICARAGUA; VALLE DE JALAPA